Cardiac Catheterization and Outcomes for Elderly Patients Hospitalized With Heart Failure - Palak Patel; Ivan Richard; Giuseppe Filice; Ivan Nikiforov; Priyaranjan Kata; Anish Kumar Kanukuntla; Arthur Okere; Christopher S Hollenbeak; Pramil Cheriyath (SAGE Publishing, 2024)
Background: Heart failure affects over 6 million people in the United States (US) with limited evidence to support the use of cardiac catheterization. The benefit of its use remains mostly as expert opinion. This study intends to assess the benefits and risks of cardiac catheterization in elderly patients admitted for heart failure. Methods: This was a retrospective study using data from the National Inpatient Sample, including admissions 65 years and older hospitalized for heart failure, between 2008 and 2016. The outcomes analyzed were in-hospital mortality, total hospital costs, and length of stay. Results: After controlling for covariates, cardiac catheterization was found to have a protective association with mortality (OR 0.87, 95% CI 0.833-0.912, P  < .0001), an increased hospital length of stay by 2.88 days (95% CI: 2.84-2.92 days, P  < .0001) and approximately $16 255 increase in cost. Conclusions: Cardiac catheterization was associated with decreased in-hospital mortality, longer length of stay and higher total costs in admissions with heart failure aged 65 years or older.